Evaluation of the ethanol intake on the Calomys callosus seminal vesicle structure - Martinez, M.; Reis, G. S.; Pinheiro, P. F. F. [UNESP]; Almeida, C. C. D. [UNESP]; Cagnon, V. H. A.; Mello Júnior, Wílson de [UNESP]; Pereira, S. [UNESP]; Padovani, C. R. [UNESP]; Martinez, Francisco Eduardo [UNESP] (Pergamon-Elsevier B.V. Ltd, 2008)
The effects of chronic alcohol ingestion on the structure of the glandular epithelium of the seminal vesicle of the rodent Calomys callosus were analyzed in 24 adult animals aged 3 months divided into three experimental groups. The control group received a solid diet and tap water, the alcoholic group received the same solid diet and ethanol P.A. diluted 20% in water (v/v) for 4 months. The abstinent group received the same liquid diet of the alcoholic one for the same period and after that the alcoholic diet was changed by water for a period of 3 months. After treatment, all animals were anesthetized, weighed and sacrificed. At the end of treatment, mean body weight did not differ between animal groups. The glandular epithelial cells of the alcoholic and abstinent groups showed atrophy and ultrastructural alterations such as the presence of altered nuclei, intense dilatation of the cisterns of the granular endoplasmic reticulum, intense digestive vacuoles and lipid droplets. Ethanol ingestion provokes marked lesions on the epithelium of the seminal vesicle probably interfering on the glandular secretion. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: alcohol; seminal vesicle; epithelium; alcoholism; Calomys callosus